An Aquifer Reflections on Deep Clay Conditions for Water Quantity Assessments - Musa, Sabariah; Zakaria, Nor Azazi; Liang, Lau Tze (International Journal of Integrated Engineering, 2014)
This study aims to evaluate the on-site testing of deep clay area through the well response and aquifer reflection analysis. The analysis was conducted using AQTESOLV software on pumping and recovery data to determine the well responses and aquifer characteristics of deep clay area. A simple experimental model was installed at the site using deep well of REWES (Recharge Well System) model assists with four monitoring wells around the model. The monitoring wells were located at 4m, 10m, 20m and 35m from the model. The site has been identified identified to have the unconfined aquifer with deep compacted clay. Due to flatten and low flow, pumping analysis and ground water response were used to evaluate water quantity and potential prospective of circulate water cycle for urban stormwater management. As reflection on water cycle, almost 20% from withdrawal capacity able to refill the ground system with limited space. It was found that the available storage, S and hydraulic conductivity, K of the clayey area are 0.001 and 32 m/day respectively. Therefore, the response on water cycle indicate some potential space to restore and withdrawal at peak time and thus, the water can be used in safely conditions.